Global Outsourcing and Offshoring An Integrated Approach to Theory and Corporate Strategy - Contractor, Farok J.; Kumar, Vikas; Kundu, Sumit K.; Pedersen, Torben (Cambridge University Press, 2010)
Global Outsourcing and Offshoring deals with some of the most fundamental structural and organizational issues facing many companies today. It considers two key strategic decisions, firstly Outsourcing: which activities or functions should be kept in-house versus outsourced; and Offshoring: in which nation is a particular function or operation best performed? These are interrelated and simultaneous decisions that are changing the spatial and organizational configuration of entire industries. The book integrates academic theories from diverse fields, including Economics, Strategy , and Industrial Organization. Contributions are drawn from scholars from 11 nations, who relate theory to practice in the pharmaceutical, automobile, medical records, appliances, human resource management, and telecommunications fields.